PPy@Fe3O4 nanoparticles inhibit the proliferation and metastasis of CRC via suppressing the NF-κB signaling pathway and promoting ferroptosis - Yu, Zhilong; Tong, Shanshi; Wang, Chenyi; Wu, Zizhen; Ye, Yingjiang; Wang, Shan; Jiang, Kewei (Frontiers in Bioengineering and Biotechnology, 2022)
Colorectal cancer (CRC) is one of the most common cancers of the digestive tract, and patients with advanced-stage cancer have poor survival despite the use of multidrug conventional chemotherapy regimens. Intra-tumor heterogeneity of cancerous cells is the main obstacle in the way to effective cancer treatments. Therefore, we are looking for novel approaches to eliminate just cancer cells including nanoparticles (NPs). PPy@Fe3O4 NPs were successfully synthesized through a portable method. The characterization of transmission electron microscopy (TEM), Fourier-Transformed infrared spectrometer, and X-ray powder diffraction have further proved successful preparation of PPy@Fe3O4 NPs. NIR irradiation was used to test the photothermal properties of NPs and an infrared camera was used to record their temperature. The direct effects of PPy@Fe3O4 NPs on colorectal cancer cell DLD1 were assessed using CCK8, plate clone, transwell, flow cytometry, and western blotting in CRC cell. The effect of PPy@Fe3O4 NPs on neoplasm growth in nude mice was evaluated in vivo. This study demonstrated that PPy@ Fe3O4 NPs significantly inhibit the growth, migration, and invasion and promote ferroptosis to the untreated controls in colorectal cancer cells. Mechanical exploration revealed that PPy@Fe3O4 NPs inhibit the multiplication, migration, and invasion of CRC cells in vitro by modulating the NF-κB signaling pathway. Importantly, Ferroptosis inhibitors Fer-1 can reverse the changes in metastasis-associated proteins caused by NPs treatment. Collectively, our observations revealed that PPy@Fe3O4 NPs were blockers of tumor progression and metastasis in CRC. This study brought new insights into bioactive NPs, with application potential in curing CRC or other human disorders.